Model Pembelajaran Studi Teks di Madrasah Muallimin Muallimat Pondok Pesantren Sunan Drajat dan Kontribusinya terhadap Kemampuan Membaca Kitab Kuning bagi Siswa - M. Fathor Rohman; Siswadi (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2020)
The Sunan Drajat Islamic Boarding School is an Islamic educational institution that consistently has the mission of producing students who have competence in the religious sciences (tafaqquh fiddin). In this Islamic boarding school, it was found that several institutions including the Muallimin Muallimat (MMA) institution, the MMA institution, students were trained to have competence in studying and reviewing Arabic texts, especially the yellow book. In order to realize this mission, mastery of Arabic grammar becomes a very important part. Because of this, MMA made analytical studies of Nahwu (syntax) and Shorof (morphology) a mandatory menu which was integrated into the curriculum as Text Studies. In this study, researchers conducted an investigation to find a formulation of Text Study learning in MMA by conducting a study of the learning stages from planning, implementation, to evaluation of Text Studies learning. The method used in this research is descriptive qualitative method that seeks to collect as much information as possible through documentation, interviews, and observations to be further studied and analyzed and draw the final result in the form of conclusions. The conclusions obtained as a result of this research are (1) Text study learning planning at MMA is formulated in the form of material distribution in reference books (Matnu al Ghoyah wa Attaqrib and Fathul Qorib); (2) The implementation of Text Studies learning at MMA includes 4 stages based on grade levels including: opening, core activity 1, core activity 2, closing; (3) evaluation of Text Studies learning in MMA uses test and non-test techniques, and evaluation of learning is applied comprehensively and intact because the evaluation is carried out in the cognitive, psychomotor and affective domains